The measurement of microwave absorption characteristics of nanocomposites using a coaxial line technique - Teber, Ahmet; Bansal, Rajeev; Ünver, Ibrahim Saim; Mehmedi, Zilhicce (World Scientific Publishing Co. Pte. Ltd., 2018)
Microwave absorption properties (MAP) of manganese soft spinel ferrite (MnFe2O4) nanoparticles (MSF NPs) mixed with multi-walled carbon nanotubes (MWCNTs) and molded as toroid-shaped pellets were experimentally studied using a coaxial line technique in the frequency range of 2-18 GHz. We used the coaxial line technique because of the smaller sample size, a wider frequency range, and a uniform cross section. The MAP were derived from the measured constitutive parameters, according to the transmission line theory. The results indicate that MWCNTs blended with ferrite nanoparticles represent a promising choice for broadband microwave absorbing materials. © 2020 Elsevier B.V., All rights reserved.
Keywords: Composites; Dielectric and magnetic properties; Radar absorbing materials